Guidelines for the Development of Good Governance-Based Supply Management for School Administrators Educational Institutions Under the Office of the Secondary Education Area, Phitsanulok, Uttaradit - Kongtui, Pimtrakarn; Siputta, Tussana (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were to study 1) the current conditions of supplies management based on the principles of good governance, 2) the problems in supplies management based on the principles of good governance, and 3) the guidelines for developing supplies management based on the principles of good governance of school administrators under the Secondary Educational Service Area Office Phitsanulok– Uttaradit. The research was conducted in two phases. Phase 1 studied the conditions and problems of supplies management. The informants consisted of 114 heads of supply officers and supply officers selected by purposive sampling. The research instrument was a five-point Likert scale questionnaire. Data were analyzed using mean and standard deviation. Phase 2 explored the development guidelines through in-depth interviews with three experts selected by purposive sampling. Data were analyzed using content analysis. The findings revealed that 1) the overall conditions of supplies management based on good governance principles were at a high level. The highest mean score was found in maintenance and inspection, while the lowest was in storage. 2) The overall problems in supplies management were found at the lowest level. The most significant problem was in disposal of supplies, while the least problematic area was maintenance and inspection. 3) The proposed guidelines for development included promoting participation of all stakeholders in implementing and monitoring procurement plans, assigning and monitoring responsibilities clearly, evaluating supplies storage, raising awareness of officers’ duties in compliance with regulations, allocating budgets for maintenance, reviewing maintenance plans regularly, and ensuring that supplies disposal aligns with the disposal plan